Antimalarial Activity of n-Hexane, n-Butanol Fractions of Spilanthes filicaulis in Swiss Mice Infected with Plasmodium berghei - Ofeniforo, Bankole Emmanuel; Ogunro, Olalekan, Bukunmi; Adeyiola, Ibikunle Oluwaseun; Balogun, Elizabeth Abidemi (Journal of Parasite Science, 2025)
Malaria, a serious disease that can be fatal if left untreated, is caused by Plasmodium parasites. Malaria poses a significant life threat due to growing parasite resistance to drugs and the prohibitive cost of treatment, particularly in high-prevalence African countries. The prospect offered by the exploration of botanicals as alternatives necessitated this study to examine the antimalarial activities of the n-hexane fraction of Spilanthes filicaulis (HFSF) and its butanol fraction (BFSF) on Plasmodium berghei-infected mice. Swiss mice of both genders were infused with a chloroquine-sensitive P. berghei (NK-65) strain intraperitoneally. Antimalarial activity (in vivo) of S. filicaulis fractions was evaluated against early and established infection employing 4-day suppressive and curative antimalarial models at 250, 500 and 750 mg/kg dose levels respectively. Rectal temperature (RT), packed cell volume (PCV), body weight (BW), parasitemia level and mean survival time (MST) were variables determined. Findings herein demonstrated marked prevention of BW, RT, and PCV reduction at the treated doses relative to the untreated controls. Moreover, both fractions significantly suppressed parasitemia dose-dependently. The highest antimalarial chemosuppression was demonstrated by the HFSF producing 60.59%, 69.29% and 71.17% inhibition in the 4-day suppression and the BFSF yielded 45.44%, 43.96% and 47.97% chemosuppression in the curative, at the treated doses respectively. Similarly, the fractions delayed the mean survival duration of treated infected mice relative to the untreated group. Therefore, the results herein suggest that both fractions demonstrate dose-dependent and statistically significant suppression of parasitemia and improved clinical parameters in mice infected with P.berghei against murine malaria.